2007
DOI: 10.1038/sj.jcbfm.9600404
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Evidence of Cytotoxic Cerebral Edema in Acute Mountain Sickness

Abstract: The present study applied T2- and diffusion-weighted magnetic resonance imaging to examine if mild cerebral edema and subsequent brain swelling are implicated in the pathophysiology of acute mountain sickness (AMS). Twenty-two subjects were examined in normoxia (21% O2), after 16 hours passive exposure to normobaric hypoxia (12% O2) corresponding to a simulated altitude of 4,500 m and after 6 hours recovery in normoxia. Clinical AMS was diagnosed in 50% of subjects during hypoxia and corresponding headache sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
137
2
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(165 citation statements)
references
References 34 publications
25
137
2
1
Order By: Relevance
“…Laboratory investigations of the brain in AMS show that all subjects exposed to altitudes of 4500 m had normal lumbar cerebrospinal fluid pressure and a small increase of brain volume assessed using MRI (<1%, ∼7-10 mL) after 16 h, independent of presence or absence of AMS [14]. The volume increase can partly be attributed to increased blood volume and partly to cell swelling [14,15]. A recent study demonstrated swelling of white matter correlating with AMS scores after 22 h [16].…”
Section: Ams and Hacementioning
confidence: 97%
See 2 more Smart Citations
“…Laboratory investigations of the brain in AMS show that all subjects exposed to altitudes of 4500 m had normal lumbar cerebrospinal fluid pressure and a small increase of brain volume assessed using MRI (<1%, ∼7-10 mL) after 16 h, independent of presence or absence of AMS [14]. The volume increase can partly be attributed to increased blood volume and partly to cell swelling [14,15]. A recent study demonstrated swelling of white matter correlating with AMS scores after 22 h [16].…”
Section: Ams and Hacementioning
confidence: 97%
“…However, in AMS, lumbar punctures reveal an intact blood-brain barrier for large molecular weight proteins [38]. Furthermore, there are no significant associations of peripheral oedema [39], slight increase in brain volume [14], albuminuria [40] and leakage of fluorescent dye from retinal vessels [41] with AMS. Thus, the slight tissue swelling in the body in hypoxia is not different between those with and without AMS.…”
Section: Hypoxaemiamentioning
confidence: 99%
See 1 more Smart Citation
“…Two MRI studies provided evidence for brain swelling in the white matter after 6 to 16 hours of passive exposure to normobaric hypoxia (inspiratory O 2 fraction, FiO 2 = 0.12). 3,4 Changes in apparent diffusion coefficient (ADC, characterizing the selfdiffusion of water in tissue) of the gray matter 5 and an increase in the total brain parenchyma volume 6 have also been reported within minutes (o 40 minutes) of hypoxia. The kinetics of cerebral volume changes and their relationships with alteration in ADC and cerebral blood flow (CBF) in hypoxia remain to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…2,7 Although the 'tight-fit' hypothesis suggests that increased brain volume and subsequent enhanced intracranial pressure may underlie AMS symptoms, 7 the link between changes in brain volumes, signs of cerebral edema, and symptoms of AMS typically developing over the first 6 to 12 hours of hypoxic exposure remains controversial. 3,4,[8][9][10] Some reports suggest that performing physical activity during the first hours of hypoxic exposure may accentuate symptoms of AMS. [11][12][13] Only one recent study compared the effects of hypoxic exposure for 8 hours associated or not with physical exercise (3 times 30 minutes of moderate intensity exercise) on brain volume and cerebral edema.…”
Section: Introductionmentioning
confidence: 99%